Tantangan Pembelajaran Sejarah di Era Globalisasi - Hermanu Joebagio (Universitas Negeri Yogyakarta, 2017)
AbstractThe impact of globalization both positive and negative is not only felt in the economic, social, and political. The existence of globalization also gives a significant influence in education. The purpose of writing this article is to know the position of learning history in the world of education in the era of globalization and explain the learning of history as an alternative inspiration history in the era of globalization. With historical complexity, and globalism already engulfing the world, it is necessary to consider innovations in historical learning, namely: (1) Drawing past red threads into present-day projection. The dark past and the good must be the basis of our projection to see how far the policy that has been done shows the right action. (2) The era of globalism is an open era that requires us to build an awareness that the national heritage of today's painted country is reflected in the social structure as well as the cultural structure. Both structures are local aspects admired by other nations, and should not be destroyed, but must be revitalized to confront globalism. Keywords: learning history, globalization, innovation